Interwar Crossroads (transcript Verlag, 2024)
Studying the entangled histories of the areas conceptualized as Middle Eastern and North Atlantic World in the interwar years is crucial to understanding the two areas' respective and common histories until today. However, many of the manifold connections, exchanges, and entanglements between the areas have not received thorough scholarly attention yet. The contributors to this volume address this by bringing together various innovative and interdisciplinary approaches to the topic. They thereby further the understanding of the two areas' entangled histories and diversify prevailing concepts and narratives. Through this, the volume also offers enriching insights into the global history of the early 20th century.